Penerapan Bimbingan Kelompok Dengan Metode ningkuk'an Dalam Meningkatkan Interaksi Sosial Remaja - Avilla Akbar; Suryati Suryati; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
This study entitled "Application of Group Guidance with ningkuk'an method in improving social interaction in Pulokerto sub-district" this research is very useful in adolescents who have not increased their social interaction. Therefore, adolescents really need group guidance with the ningkuk'an method to help them improve interaction and communicate well. This research is a field research using qualitative research methods The results of this study show (1) before group guidance was carried out with the ningkuk'an method, adolescents had not created interaction and were still reduced then there was no good communication, the interaction had not increased (2) the application of group guidance in increasing social interaction using the ningkuk'an method, which consisted of 4 stages, namely beginning, transition, end. After the group guidance using the ningkuk'an method showed an increase